Textural and Shelf-life Improvement of Khanom Bua Loi Dough, Using Modified Starch - แย้มบรรจง เปรมฤทัย (Progress in Applied Science and Technology, 2016)
Khanom Bualoi dough, a small rounded mass of glutinous rice flour sold in the market, could not be kept for long. It became hard at core and black velvety molds after keeping for 2 days at room temperature. The objectives of this research were to improve a blended starch of good quality and shelf-life for Khanom Bualoi production. Starch ethers of 5, 10 and 15 percents were mixed with glutinous rice flour and boiling water into dough. The starch mixture was then added to 5, 10 and 15% humectants and 1% calcium propionate as preservative. Dough with 10% added humectants was good quality and accepted by panelists. It could be kept for 6 days in polypropylene bag at room temperature without appreciable changes. The approximate analysis showed that Khanom Bualoi was found to contain mostly carbohydrate. The production cost of Khanom Bualoi was 0.033 baht per gram.